Comparison of Motivational Climate Between Male and Female Athletes in Team and Individual Sports - Siti Muhimaturohmah; Yati Ruhayati; Kuston Sultoni (Gladi : Jurnal Ilmu Keolahragaan, 2025)
- This study aims to compare perceptions of motivational and emotional regulation as forms of self-regulation between male and female athletes and between team and individual sport athletes. The research design uses a comparative quantitative approach involving 115 active athletes from various sports. Measurements were conducted using the PMCSQ-2 and IERQS instruments, both of which showed very high reliability, with a Cronbach’s Alpha value of 0.932. Data analysis included Kolmogorov-Smirnov normality test and independent sample t-test to identify differences between groups. The result showed no significant differences between male and female athletes on the variables of motivational climate (M = 124.35 vs. 121.98; p = 0.507), ego-involving climate (p = 0.202), task-involving climate (p= 0.6888), and emotion regulation (p= 0.778). the same pattern was seen in comparison between team and individual athletes, where no significant differences were found in motivational climate (p = 0.747), ego climate (p = 0.223), task climate (p = 0.326), or emotion regulation streategies including reappraisal (p = 0.238) and suppression (p = 0.950). these findings indicate that gender and sport type different do not affect athletes’ perceptions of motivational climate or emotional regulation abilities, suggesting that their psychological experiences are more included by uniform coaching patterns, coaching styles, and social environments. The practical implications of this study confirm strategies can be designed universally and inclusively for all athletes, regardless of gender or sport type to research should consider other contextual variables and apply a longitudinal design to obtain a more comprehensive picture of the psychological dynamites of athletes over time.